2020
DOI: 10.1111/plb.13157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maize–alfalfa intercropping on the physiological characteristics, nitrogen uptake and yield of maize

Abstract: In Northeastern China, the intensive cropping system and increased use of chemical fertilizer has caused severe problems in terms of sustainable agricultural development. Therefore, to improve agricultural sustainability and crop productivity the farming system needs to be modified in the region. A pot experiment was conducted to evaluate the effect of maize–alfalfa intercropping on the physiological characteristics, nitrogen (N) uptake and yield of the maize crops in northeast China in 2017–2018. The study fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 43 publications
7
26
0
Order By: Relevance
“…Taking together, compared to the introduced cultivars, the indigenous cultivars showed more extensive variability. Overall, winter hardiness can be used as a reliable metric in screening cold-resistant alfalfa cultivars for integration into the regional agroecosystems in the face of climate change [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking together, compared to the introduced cultivars, the indigenous cultivars showed more extensive variability. Overall, winter hardiness can be used as a reliable metric in screening cold-resistant alfalfa cultivars for integration into the regional agroecosystems in the face of climate change [37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the successful establishment of alfalfa can provide bulk quantities of high-quality protein forage for animal husbandry, especially for the development of the dairy industry [5,37,40,[43][44][45]. On the other hand, the forage-crop rotation can improve the soil quality, especially in saline-alkaline land, or medium-to low-yielding land areas, which plays a great role in improving soil fertility, consolidating farmland quality, and ensuring food safety and stable production [37,38,43,[46][47][48]. The world is entering an era of low-carbon economy.…”
Section: Discussionmentioning
confidence: 99%
“…The application of fertilizers, especially nitrogen and phosphorus which have great promotion to grain yield of, remains essential for food security. However, the loss of N and P from agroecosystems results in environmental problems and threatens the sustainability of agricultural practices ( Nasar et al, 2020 ). This concern has been considered one of the major challenges to feed the world in 2050 ( Ehrlich & Harte, 2015 ; Mueller et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the best nutrient intake was 50% YM + 50% urea with the highest total yield result of 12,749.50 kg per ha. It is suggested that another treatment to control weed and nitrogen fixation be added to provide sustainable nutrients (Nasar et al, 2020), and some plant regulators such as Salicylic acid as a hormone be given for maize growth and yield (Arshad et al, 2020). Meanwhile, the soil temperature management technologies can increase agricultural productivity and sustainability while reducing environmental impact (Cameron et al, 2013).…”
Section: Crop Productionmentioning
confidence: 99%